Targeted Polymer–Peptide Conjugates for E-Selectin Blockade in Renal Injury - Nenad Milošević; Marie Rütter; Yvonne Ventura; Valeria Feinshtein; Ayelet David (Pharmaceutics)
Background/Objectives: Leukocytes play a significant role in both acute kidney injury (AKI) and chronic kidney disease (CKD), contributing to pathogenesis and tissue damage. The process of leukocyte infiltration into the inflamed tissues is mediated by the interactions between the leukocytes and cell adhesion molecules (CAMs, i.e., E-selectin, P-selectin, and VCAM-1) present on the inner surface of the inflamed vasculature. Directly interfering with these interactions is a viable strategy to limit the extent of excessive inflammation; however, several small-molecule drug candidates failed during clinical translation. We hypothesized that a synthetic polymer presenting multiple copies of the high-affinity E-selecting binding peptide (P-Esbp) could block E-selectin-mediated functions and decrease leukocytes infiltration, thus reducing the extent of inflammatory kidney injury. Methods: P-Esbp was synthesized by conjugating E-selecting binding peptide (Esbp) to N-(2-hydroxypropyl)methacrylamide (HPMA) copolymer with reactive ester groups via aminolysis. The effects of P-Esbp treatment on kidney injury were investigated in two different models: AKI model (renal ischemia—reperfusion injury—RIRI) and CKD model (adenine-induced kidney injury). Results: We found that the mRNA levels of E-selectin were up-regulated in the kidney following acute and chronic tissue injury. P-Esbp demonstrated an extended half-life time in the bloodstream, and the polymer accumulated significantly in the liver, lungs, and kidneys within 4 h post injection. Treatment with P-Esbp suppressed the up-regulation of E-selectin in mice with RIRI and attenuated the inflammatory process. In the adenine-induced CKD model, the use of the E-selectin blocking copolymer had little impact on the progression of kidney injury, owing to the compensating function of P-selectin and VCAM-1. Conclusion: Our findings provide valuable insights into the interconnection between CAMs and compensatory mechanisms in controlling leukocyte migration in AKI and CKD. The combination of multiple CAM blockers, given simultaneously, may provide protective effects for preventing excessive leukocyte infiltration and control renal injury.